The Potential Role of Soil Bacteria as an Indicator of Heavy Metal Pollution in Southern, Iraq - Raghad Shubbar Jaafar (مجلة بغداد للعلوم)
The present study was performed to spotlight the potential role of soil bacteria in the Al-Rumaila oil field as a bioindicator of heavy metals pollution. For this purpose, nine soil samples were collected from different sites, with 20cm depth, to assess the pollution status depending on the total and available concentrations of heavy metals.  The result indicates pollution of the studied soils with the following metals: Cd, Cu, Fe, Zn, and Pb. The mean of total concentration for all studied metals was higher than the allowed maximum limit based on the international limit:(3.394, 3.994, 39.993, 8844.979,150.372, and 103.347 µg/g), respectively. While measuring the total Metal concentration is important in determining the degree of pollution in the environment; it cannot be depended to determine their impact on the living organisms. In the present study the means of available concentration of studied metals were as follows: 0.015, 0.787, 0.021, 0.515, and4.304 µg/g. respectively, which were lower than their total concentration. Different types of bacterial genera (Serratia marcescens, Sphingomonas paucimobilis, Bacillus subtilis, Pseudomonas aeruginosa, and Staphylococcus lentus) were isolated from the same soil. And broadcasts through the results their presence in all studied soils. Therefore, the isolated bacteria play a significant role as an indicator of metal pollution in the soil, which was proved through the result of the Minimum inhibitor concentration (MIC), which indicated a high tolerance ability towered these metals.